2012
DOI: 10.1002/ffj.3112
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of volatile flavour compounds from butter oil in a low‐density polyethylene membrane pouch

Abstract: A low‐density polyethylene membrane pouch method was developed to extract volatile flavour compounds from butter oil prior to gas chromatography–mass spectrometry analysis. The butter oil represented oil‐based sample with complex flavour compounds. It was placed in the pouch and heat‐sealed for extraction in diethyl ether at 40°C for 1 h. The extraction mechanism can be explained by the molecular sieve effect. The extracted volatile flavour compounds are essential for butter oil aroma, e.g. fatty acids and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…2). Despite the high proportion of acids, we found that long‐chain fatty acids (C 12 ‐C 18 ) were the major acidic compounds of SFE‐derived FEOE, which had high odor thresholds (Kalua et al, 2007) and weak volatility that contributed less to the aroma (Chongcharoenyanon et al, 2012). In contrast, those olefins with characteristic herb aroma made up only 3.48% of the total compositions in SFE‐derived FEOE.…”
Section: Resultsmentioning
confidence: 91%
“…2). Despite the high proportion of acids, we found that long‐chain fatty acids (C 12 ‐C 18 ) were the major acidic compounds of SFE‐derived FEOE, which had high odor thresholds (Kalua et al, 2007) and weak volatility that contributed less to the aroma (Chongcharoenyanon et al, 2012). In contrast, those olefins with characteristic herb aroma made up only 3.48% of the total compositions in SFE‐derived FEOE.…”
Section: Resultsmentioning
confidence: 91%
“…In addition, the extraction of odorants is mostly accompanied by the extraction of lipids, often limiting the use of simple liquid–liquid extraction (LLE). Hence, flavor compounds in rapeseed oil require preseparation, such as the use of a membrane as a molecular sieve to separate triglycerides from the remaining oil constituents (Chongcharoenyanon et al., 2012). Not any existing solvent‐extraction approach provides complete isolation of flavor compounds.…”
Section: Flavor Analysis Techniques Of Rapeseed Oilmentioning
confidence: 99%
“…Sci. 2023, 13 includes extensive syrup heating and drying-solidification steps with continuous agitation [1]. The thermal process, especially the final heating stage at temperatures between 100-140 • C, facilitates a non-enzymatic browning mechanism, known as the Maillard reaction, in the solidified mixture [1][2][3].…”
Section: Introductionmentioning
confidence: 99%